The stigma of recasting: Martínez Sierra and their adaptation of the hagiographic play La adúltera penitente - Rodríguez-Gallego, Fernando (Talía. Revista de estudios teatrales, 2020)
One of the first plays that Gregorio Martínez Sierra put on stage in the Teatro Eslava was La adúltera penitente, a hagiographic play written in collaboration by Juan de Matos Fragoso, Jerónimo de Cáncer and Agustín Moreto. The play, based upon the legend of Saint Theodora of Alexandria, may have attracted María Martínez Sierra’s attention because of its conventual environment and the saint’s selflessness. Before its premiere, Gregorio delivered a conference in which he exalts the values of freedom of the golden age theatre against the tyranny of verisimilitude in the contemporary. Therefore, in his adaptation he proposed to respect those values and escape the principle of recasting, which conformed the golden age plays to the conventions of the theatre of that time. This article studies how this adaptation, however, is incapable of respecting the scenic freedom of the original, and also incurs the recast principle that was intended to be avoided.